Missed chances and unfulfilled hopes: Why do firms make errors in evaluating technological opportunities? - Kumar, Amit; Operti, Elisa (Strategic Management Journal, 2023)
Abstract Research Abstract This study examines commission and omission errors in the evaluation of technological opportunities. Integrating structural and cognitive perspectives, we propose that inventors with more cohesive collaboration networks within the firm or geographically closer to the corporate headquarters exert greater influence on the dominant representations shaping opportunity evaluation within the firm. Thus, their inventions are more likely to be positively assessed, even if quality considerations suggest otherwise. Conversely, even when superior in quality, inventions from individuals with less cohesive collaboration networks within the firm or located far from the corporate headquarters are less likely to be positively evaluated, leading to omission errors. The study provides evidence based on 22 interviews and archival data from the mobile phone and personal digital assistant industry between 1990 and 2010. Managerial Abstract This study examines commission and omission errors in decision‐making about technologies. Studying patent renewal decisions of 42 firms in the mobile phone and personal digital assistant industry between 1990 and 2010, we show that inventors with more cohesive collaboration networks within the firm or located close to the corporate headquarters have their inventions positively assessed even when of lower quality, leading to commission errors. On the other hand, inventors with less cohesive collaboration networks within the firm or located far away from the corporate headquarters have their inventions disregarded even when of higher quality, causing omission errors. These findings call for managerial vigilance in technology evaluation decisions, ensuring valuable ideas are not overlooked due to an inventor's network position or location.